Evidence for cross-bridge order in contraction of glycerinated skeletal muscle. - Burghardt, T P (1983)
The linear dichroism of iodoacetylrhodamine labels attached to the single reactive thiol groups of myosin heads was measured to determine the spatial orientation of myosin cross-bridges in single glycerinated skeletal muscle fibers. We have shown previously that in rigor the chromophoric labels are well ordered and assume an orientation nearly perpendicular to the fiber axis; in the presence of MgADP, a large fraction of probe remains well ordered but the probe attitude assumes a more slanted orientation; in relaxed muscle, the probe order is largely lost, implying a high degree of cross-bridge disorder. In this paper, we report that during isometric contraction a large fraction of the probe shows a high degree of order, suggesting the attachment of approximately equal to 65% of the cross-bridges to actin. These ordered cross-bridges have a probe attitude similar to that of the MgADP-induced static state and hence are in a mechanical state quite distinct from rigor.